Tell no one who you are : the hidden childhood of Régine Miller - Buchignani, Walter (Tundra Books, 1994)
Describes the life of a Jewish girl who is sent into hiding and is moved through four Belgian households, only to eventually learn of the magnitude and horror of the Holocaust.